Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.2337/dc19-1061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gender-Affirming Hormone Therapy on Insulin Sensitivity and Incretin Responses in Transgender People

Abstract: The long-term influences of sex hormone administration on insulin sensitivity and incretin hormones are controversial. We investigated these effects in 35 transgender men (TM) and 55 transgender women (TW) from the European Network for the Investigation of Gender Incongruence (ENIGI) study. RESEARCH DESIGN AND METHODSBefore and after 1 year of gender-affirming hormone therapy, body composition and oral glucose tolerance tests (OGTTs) were evaluated. RESULTSIn TM, body weight (2.8 6 1.0 kg; P < 0.01), fat-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 43 publications
8
56
0
1
Order By: Relevance
“…40 Moreover, testosterone also inhibits lipoprotein lipase activity in adipocytes, an enzyme that increases fat deposition by decreasing adipose tissue lipolysis. 14 We found no significant difference in insulin resistance between trans men and cisgender female controls, in keeping with all but one prior study in transgender men that showed either no cha nge [27][28][29][31][32][33][34][35][36][37]41 or a decrease 30,39 in insulin resistance. All these studies were prospective longitudinal in design but only one had a control group.…”
Section: Masculinising Hormone Therapysupporting
confidence: 85%
“…40 Moreover, testosterone also inhibits lipoprotein lipase activity in adipocytes, an enzyme that increases fat deposition by decreasing adipose tissue lipolysis. 14 We found no significant difference in insulin resistance between trans men and cisgender female controls, in keeping with all but one prior study in transgender men that showed either no cha nge [27][28][29][31][32][33][34][35][36][37]41 or a decrease 30,39 in insulin resistance. All these studies were prospective longitudinal in design but only one had a control group.…”
Section: Masculinising Hormone Therapysupporting
confidence: 85%
“…We have demonstrated remarkable responses (clinical exam, mammography, ultrasound) of hormone receptor positive tumors to T + aromatase inhibitor implant therapy in the neoadjuvant setting, further confirming the direct beneficial effect of T at the AR [8,9]. T also improves glycemic control and attenuates the inflammatory process, both of which could have a beneficial effect on the incidence of breast cancer [14,15,32,33].…”
Section: Discussionsupporting
confidence: 58%
“…Most notably, in our patient population, mean serum T level when symptoms returned (trough) was 171 + 73 ng/dl, well above endogenous ranges, with significant inter-individual variation (CV 42.6%). In regard to safety, long-term studies on transgender men have shown that even higher (male) doses of T do not increase the risk of cardiovascular events, stroke, or cancer; T therapy also increases insulin sensitivity, as opposed to estrogen therapy in transgender women [32,37,38]. No other hormone medication (e.g., insulin, estrogen) is dosed or micromanaged based solely on levels of the active pharmacologic ingredient in serum, but rather on clinical response/beneficial effects versus adverse side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The increases in body weight, particularly fat mass, in transgender women may explain why GAHT is associated with increased CVA and CVD in transgender women but not in transgender men [12] . Increases in fat mass in transgender women as compared to transgender men may also predispose transgender women to increased risk of metabolic syndrome [13] , [14] .…”
Section: Introductionmentioning
confidence: 99%